Pesquisa de anticorpos contra Leptospira spp. em animais silvestres e em estado feral da região de Nhecolândia, Mato Grosso do Sul, Brasil: utilização da técnica de imuno-histoquímica para detecção do agente - Girio, Raul José Silva [UNESP]; Pereira, Fernando Lúcio Garcia [UNESP]; Marchiori Filho, Moacir; Mathias, Luís Antônio [UNESP]; Herreira, Rita De Cássia Pereira; Alessi, Antônio Carlos [UNESP]; Girio, Thaís Marino Silva (Universidade Federal de Santa Maria, 2004)
Three hundred and fifteen serum samples of several animal species living in wild or in feral state in the area of Nhecolândia, Corumbá, MS, Brazil, were examined by the microscopic agglutination test. Of these samples, 67 were of feral bovine (Bos taurus indicus), 39 of feral pigs (Sus scrofa), 39 of buffaloes (Bubalus bubalis), nine of coatis (Nasua nasua), 41 of pampas deer (Ozotoceros bezoarticus), 10 of brocket deer (Mazama americana) and 110 of feral sheep (Ovis aries). In 12 dead animals (six feral pigs, four pampas deer and two feral sheep), isolation attempts and Leptospira identification through the immunohistochemistry were accomplished. Sixty-four (20.3%) of the samples reacted to at least one serovar of pathogenic Leptospira; 41.0% of the buffaloes, 40.3% of the feral bovine, 17.9% of the feral pigs, 9% of the feral sheep, and 9.7% of the pampas deer serum samples were reactors. All the serum samples of brocket deer and of coatis were not reactors. The most frequent serovars for the studied animal species were: pomona for buffaloes and feral sheep; icterohaemorrhagiae for feral sheep, pampas deer and feral pigs; and copenhageni for pampas deer and feral pigs. The attempts of Leptospira isolation resulted negative, and the immunohistochemistry analysis revealed Leptospira in the liver of one feral pig. Microscopic examination of the kidney revealed vascular congestion, hemorrhage and infiltration of mononuclear inflammatory cells in the interstice.

Foram examinadas 315 amostras de soros sangüíneos de diversas espécies de animais que vivem em estado feral ou silvestre na região de Nhecolândia, Corumbá, MS, por meio da prova de soroaglutinação microscópica para leptospirose. Dessas amostras, 67 foram de bois baguás (Bos taurus indicus), 39 de porcos-monteiros (Sus scrofa), 39 de búfalos (Bubalus bubalis), nove de quatis (Nasua nasua), 41 de veados-campeiros (Ozotoceros bezoarticus), 10 de veados-mateiros (Mazama americana) e 110 amostras de ovinos (Ovis aries). Em 12 animais que vieram a óbito, seis porcos-monteiros, quatro veados-campeiros e dois ovinos, foram realizadas tentativas de isolamento de Leptospira do fígado e dos rins por cultura em meio semi-sólido. Fragmentos desses órgãos foram submetidos a exame histopatológico e também a exame para detecção das Leptospiras pela técnica de imuno-histoquímica. Os resultados dos exames sorológicos mostraram que 64 (20,3%) das amostras foram reagentes para, pelo menos, um sorovar de Leptospira patogênica; foram reagentes 41,0% das amostras de búfalos, 40,3% das de bois baguás, 17,9% das de porcos-monteiros, 9% das de ovinos e 9,7% das amostras de veados-campeiros; nenhuma das amostras de veados-mateiros e de quatis foi reagente. Os sorovares mais freqüentes foram: pomona, para búfalos e ovinos; icterohaemorrhagiae, para ovinos, veados-campeiros e suínos; e copenhageni, para veados-campeiros e suínos. As tentativas de isolamento dos rins e fígados foram todas negativas, e pela técnica da imuno-histoquímica foi detectada Leptospira no fígado de um porco-monteiro. As principais alterações estruturais, encontradas nos rins de dois veados-campeiros e de um porco-monteiro, foram infiltrado inflamatório intersticial com congestão associada a hemorragias.
Investigation of antibodies to Leptospira spp. in wild and feral animals from the region of Nhecolândia, Mato Grosso do Sul, Brazil: use of the immunohistochemistry technique for the agent detection
Keywords: leptospirosis; wild animals; feral animals; serology; immunohistochemistry; leptospirose; animais silvestres; sorologia; imuno-histoquímica